Job burnout amongst university administrative staff members in China—a perspective on Sustainable Development Goals (SDGs) - Lei, Miao; Alam, Gazi Mahabubul; Hassan, Aminuddin (Multidisciplinary Digital Publishing Institute, 2023)
It is widely accepted that administrative staff, as important components of a university’s workforce, play a critical role in realizing the United Nations’ Sustainable Development Goals (SDGs). The worth of administrative staff is based on their productivity, and this has a significant impact on the viability of universities. Based on the job demands–resources model, this study investigates the antecedents of job burnout among administrative staff from both emotional and interpersonal perspectives, taking into account SDGs 3, 4, and 8. In this paper, a quantitative research method using descriptive and inferential analyses explores the complex interplay between job autonomy, emotional job demands, colleague support, and job burnout, with a particular emphasis on the role of emotion regulation. A questionnaire was answered anonymously by 1009 administrative staff members in China, and the results conclude that job autonomy was negatively associated with job burnout, while emotional job demands were positively linked to burnout. Moreover, leader support emerged as more beneficial to workers than colleague support. Emotion regulation strategies such as reappraisal function as an important personal resource that buffers the negative effects of job demands and enhances job resources, leading to lower levels of burnout. Furthermore, this study examines how the SDGs can be achieved through reducing job burnout. The important implications for university administrative staff and policymakers, as well as the sustainable development of universities, are discussed.